Hydroxychloroquine enhances insulin sensitivity and ameliorates abnormal lipid metabolism in obese women with polycystic ovary syndrome - Ruihan Wang; Shanqin Qi; Qi Wang; Jiajia Lang; Conghui Pang; Kehua Wang (BMC Endocrine Disorders)
Abstract Background Hydroxychloroquine (HCQ) is frequently utilized in rheumatic immune disorders and has been discovered to exert hypoglycemic effects in some obese women with polycystic ovary syndrome(PCOS), however, the precise efficacy and mechanism of action remain ambiguous. Objective To examine the impact of HCQ on glucose and lipid metabolism as well as sex hormone levels in obese women with PCOS. Method Fifty obese women with PCOS were randomly allocated into two groups: HCQ group (n = 25) and metformin (MET) group (n = 25). The HCQ group received a daily dose of 200 mg hydroxychloroquine, while the MET group received a daily dose of 1000 mg metformin. Body fat parameters, glucose and lipid metabolism levels, as well as hormone levels were evaluated. Additionally, the incidence of pregnancy within six months following treatment was also assessed. Network pharmacology was also employed to analyze the potential molecular mechanism. Result Patients in the HCQ group (n = 20) and MET group (n = 23) were ultimately included for analysis. Following treatment, both groups exhibited significant improvements in body fat distribution and glucose metabolism status, with the HCQ group demonstrating a notable advantage over the MET group in increasing insulin sensitivity index (ISI)(HCQ:1.87 ± 0.21,MET:1.75 ± 0.29). Serum lipid levels [Serum total cholesterol(TC, mmol/L)(HCQ:4.51 ± 0.87,MET:5.05 ± 0.65), triglyceride(TG, mmol/L)(HCQ:1.36 ± 0.51,MET:1.67 ± 0.72), low-density lipoprotein (LDL, mmol/L)(HCQ:2.66 ± 0.98,MET:0.47 ± 1.42),decreased in both groups post-treatment, with the HCQ group displaying clear advantages compared to the MET group. The improvement of sex hormone levels was not pronounced in either group, although there was an overall downward trend. Conclusion The potential benefits of HCQ in the management of in obese women with PCOS include significant improvements in body fat distribution, glucose and lipid metabolism levels, as well as correction of hormonal disorders. Clinical trial registration The study was officially registered as a clinical trial on April 17, 2022, with the registration number ChiCTR2200058816. https://www.chictr.org.cn/showproj.html?proj=160099 .